2017
DOI: 10.18203/2394-6040.ijcmph20173828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of open air defecation and awareness and practices of sanitary latrine usage in a rural village of Raipur district

Abstract: Background: The practice of open defecation is rampant in India and our country is home to the world’s largest population of people who defecate in the open. Insanitary disposal of human excreta, along with unsafe drinking water and poor hygiene conditions, is a leading cause of morbidity and mortality in low-income countries. The study was conducted with objective to find sanitary latrine usage, prevalence of open air defecation and awareness related to diseases caused by open air defecation in the rural popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
10
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 4 publications
(4 reference statements)
9
10
1
Order By: Relevance
“…14 In this study majority of the study participants were unaware of Government facilities of construction for toilets. This is similar to study done by Kumar et al and Panda et al 11,12…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…14 In this study majority of the study participants were unaware of Government facilities of construction for toilets. This is similar to study done by Kumar et al and Panda et al 11,12…”
Section: Discussionsupporting
confidence: 92%
“…This is similar to study conducted by Bathija et al and Bharadwaj et al 13,17 In this study majority of the study participants has sanitary latrine in their houses (52.5%). This is similar to study done by Panda et al 11 In this study 15.6% of households practiced open air defecation in spite of having toilets in their homes. This is similar to a study done by Venkateswarlu et al 14 In this study majority of the study participants belongs to >51 years of age, males were more in number and no significant association was found with open air defecation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, nearly half of the children practised (45.7%) open air defecation which is higher when compared to the findings of the study done by Anuradha in Tamilnadu which showed the prevalence of open air defecation to be 33.1% and to the findings of the study done by Panda in Raipur which showed the prevalence of open air defecation to be 23.2%. 4,5 The presence of higher prevalence of open air defection in the present study indicates that there is a gap between the knowledge level of participants regarding open air defecation and their practice of the same.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence (p) of knowledge about sanitary toilet use was found to be 60% (Sidhraj J study), q = 100-p and d for error as 5% at 95% confidence interval. 7 They were selected randomly to ascertain the validity of the questionnaire and feasibility of the study. All the persons above 12 years from each household, who were permanent residents of the village, were selected by simple random sampling technique using computer generated random table method.…”
Section: Discussionmentioning
confidence: 99%